Technology Of Composite Paints, Varnishes, And Rubber Materials - Tuxliyev Muslimbek Sherzod o’g’li (Global Scientific Publishing, 2025)
The field of composite materials, including paints, varnishes, and rubber, has undergone significant advancements in recent years, driven by the demand for highperformance, sustainable, and cost-effective solutions across industries. This paper provides a comprehensive overview of the technology behind composite paints, varnishes, and rubber materials, focusing on their composition, production processes, applications, and advancements. Challenges such as environmental concerns, cost optimization, and material compatibility are discussed, along with emerging trends and future directions in the field.
Keywords: Composite materials; paints; varnishes; rubber